Arrays of quasi-hexagonally ordered silica nanopillars with independently controlled areal density, diameter and height gradients. (24th February 2015) - Özdemir, Burcin; Huang, Wenting; Plettl, Alfred; Ziemann, Paul
Abstract: A consecutive fabrication approach of independently tailored gradients of the topographical parameters distance, diameter and height in arrays of well-ordered nanopillars on smooth SiO2 –Si-wafers is presented. For this purpose, previously reported preparation techniques are further developed and combined. First, self-assembly of Au-salt loaded micelles by dip-coating with computer-controlled pulling-out velocities and subsequent hydrogen plasma treatment produce quasi-hexagonally ordered, 2-dimensional arrays of Au nanoparticles (NPs) with unidirectional variations of the interparticle distances along the pulling direction between 50–120 nm. Second, the distance (or areal density) gradient profile received in this way is superimposed with a diameter-controlled gradient profile of the NPs applying a selective photochemical growth technique. For demonstration, a 1D shutter is used for locally defined UV exposure times to prepare Au NP size gradients varying between 12 and 30 nm. Third, these double-gradient NP arrangements serve as etching masks in a following reactive ion etching step delivering arrays of nanopillars. For height gradient generation, the etching time is locally controlled by applying a shutter made from Si wafer piece. Due to the high flexibility of the etching process, the preparation route works on various materials such as cover slips, silicon, silicon oxide, silicon nitride and silicon carbide.